Local prolonged release of antibiotic for prevention of sternal wound infections postcardiac surgery—A novel technology. Issue 10 (2nd August 2020) - Kachel, Erez; Moshkovitz, Yaron; Sternik, Leonid; Sahar, Gideon; Grosman‐Rimon, Liza; Belotserkovsky, Olga; Reichart, Malka; Stark, Yafit; Emanuel, Noam
Abstract: Introduction: Sternal wound infection (SWI) is a devastating postcardiac surgical complication. D‐PLEX100 (D‐PLEX) is a localized prolonged release compound applied as a prophylactic at the completion of surgery to prevent SWI. The D‐PLEX technology platform is built as a matrix of alternating layers of polymers and lipids, entrapping an antibiotic (doxycycline). The objective of this study was to assess the safety profile and pharmacokinetics of D‐PLEX in reducing SWI rates postcardiac surgery. Method: Eighty‐one patients were enrolled in a prospective single‐blind randomized controlled multicenter study. Sixty patients were treated with both D‐PLEX and standard of care (SOC) and 21 with SOC alone. Both groups were followed 6 months for safety endpoints. SWI was assessed at 90 days. Results: No SWI‐related serious adverse events (SAEs) occurred in either group. The mean plasma Cmax in patients treated with D‐PLEX was about 10 times lower than the value detected following the oral administration of doxycycline hyclate with an equivalent overall dose, and followed by a very low plasma concentration over the next 30 days. There were no sternal infections in the D‐PLEX group (0/60) while there was one patient with a sternal infection in the control group (1/21, 4.8%). Conclusion: D‐PLEX was found to be safe for use in cardiac surgery patients. By providing localized prophylactic prolonged release of broad‐spectrum antibiotics, D‐PLEX has the potential to prevent SWI postcardiac surgery and long‐term postoperative hospitalization, reducing high‐treatment costs, morbidity, and mortality.